Gender approach - Mena Ordoñez, Sissy Soledad (2020)
Foundation: University centers are places of construction of knowledge and the contributions to science of the university community are undeniable. Women have been taking greater participation in various areas of knowledge. Objective: to establish the scientific contribution that female university teachers have been making, as well as the barriers and opportunities, let's see the case of Tacna (Perú). Method: observational, analytical study. The research was conducted with 186 female teachers, from two universities with official headquarters in the region, who were analyzed aspects of development of research projects in relation to opportunities and barriers to produce research. Results: The area of knowledge with the greatest number of works is medical and health sciences, followed by the humanities and social sciences. The greatest number of research works occurs in the group of married women (p: 0,03), and between 40 to 59 years of age (p: 0,03), who also work in another university (p: 0,023) , The main barriers identified are household chores, lack of time, low income, scarce competitive funds. The opportunities identified are institutional funds (p: 0,00), the inclusion of teaching hours at the same university (p:0,01) and the publication of the calls on the website (p: 0,01) Conclusion: It was concluded that there are factors that favor research, but barriers were also identified.